1988
DOI: 10.1111/j.1476-5381.1988.tb10302.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in central GABAergic function following acute and repeated stress

Abstract: The function of γ‐aminobutyric acid (GABA)ergic systems in response to acute and repeated stressful manipulations was evaluated in both the corpus striatum and frontal cerebral cortex of the rat. In the corpus striatum the activity of the synthetic enzyme for GABA (glutamic acid decarboxylase, GAD) and the levels of GABA were reduced by acute immobilization stress (1 h). GABA turnover was reduced only by acute cold stress (3 h, 4°C). In the frontal cerebral cortex no changes were observed after acute stressful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(22 citation statements)
references
References 35 publications
0
22
0
Order By: Relevance
“…Several lines of evidence point on this direction. On one hand, stress exposure was shown to enhance the release of excitatory neurotransmitters (such as glutamate, dopamine, norepinephrine, or acetylcholine) in the hippocampus and PFC (Finlay et al, 1995; Mark et al, 1996; Feenstra, 2000; Moghaddam, 2002; Dazzi et al, 2004); on the other hand, it is known that GABAergic activity is reduced after stress exposure in these brain regions (Otero Losada, 1988; Hasler et al, 2010). Interestingly, once the increase in PSD is established in the vHIP, the changes in the mPFC might also be due to an augmented afferent excitatory input; in this case an early increase in the activation of hippocampal neurons could lead consequently to overactivation of monosynaptically connected (Jay and Witter, 1991; Thierry et al, 2000; Tierney et al, 2004) neurons in the mPFC.…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence point on this direction. On one hand, stress exposure was shown to enhance the release of excitatory neurotransmitters (such as glutamate, dopamine, norepinephrine, or acetylcholine) in the hippocampus and PFC (Finlay et al, 1995; Mark et al, 1996; Feenstra, 2000; Moghaddam, 2002; Dazzi et al, 2004); on the other hand, it is known that GABAergic activity is reduced after stress exposure in these brain regions (Otero Losada, 1988; Hasler et al, 2010). Interestingly, once the increase in PSD is established in the vHIP, the changes in the mPFC might also be due to an augmented afferent excitatory input; in this case an early increase in the activation of hippocampal neurons could lead consequently to overactivation of monosynaptically connected (Jay and Witter, 1991; Thierry et al, 2000; Tierney et al, 2004) neurons in the mPFC.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown that the nucleus accumbens and amygdala play prominent roles in modulation of the interoceptive effects of alcohol (Besheer et al 2003, 2009; Hodge and Aiken 1996; Hodge and Cox 1998). Thus, decreased sensitivity to the interoceptive effects of alcohol following repeated CORT exposure may be related, in part, to maladaptive changes (i.e., neurochemical, transcription, and signaling) within these limbic brain regions (Buffalari and Grace 2009; Makino et al 1994; Morales-Medina et al 2009; Otero Losada 1988; Perrotti et al 2004; Wang et al 2010). Therefore, it will be of interest for future work to determine the functional neurobiological mechanism underlying the related decreased sensitivity to the interoceptive effects of alcohol.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, it is suggested that the observed decrease in GABA concentration is likely related to a rapid down-regulation of glutamate decarboxylase associated with acute psychological stress. Glutamate decarboxylase activity and GABA concentrations are modulated during a variety of physiological and pathological conditions, including acute stress (6, 13). Previous kinetic studies performed on both animals and humans have also shown that GABA undergoes rapid turnover (3436).…”
Section: Discussionmentioning
confidence: 99%
“…Prefrontal GABA concentrations were determined using a recently developed MRS method with a 3 Tesla General Electric magnetic resonance imaging (MRI) scanner (General Electric, Milwaukee) and a homogeneous resonator coil that allowed for reliable determination of GABA levels with a temporal resolution of 8 minutes. Since stress reduces GABA levels in the medial prefrontal cortex in rat models (6), we hypothesized that the prefrontal GABA concentration would decrease following acute psychological stress in humans.…”
mentioning
confidence: 99%